Avoidant adjustment predicts lower information seeking in people with lung cancer. Issue 3 (31st January 2012) - Mulcare, Hunter; Kashima, Yoshihisa; Milgrom, Jeannette; Wheeler, Greg; Wirth, Andrew; Bishop, Michelle; Schofield, Penelope
Abstract Background Few studies have examined the factors that predict information seeking by cancer patients. This study investigated the influence of different styles of adjustment to cancer, information goals and information needs on the information seeking by lung cancer patients. Method Lung cancer patients were recruited at their first appointment with their radiation oncologist and completed two questionnaires, one month apart, containing the Patient Information Needs Questionnaire, Mini‐Mental Adjustment to Cancer Scale, the number of information sources accessed and a purpose‐built measure of cancer‐related personal goals. Results Fifty‐nine participants completed two questionnaires. The average number of information sources accessed by participants increased over the 1‐month period, from 7.2 to 9.1 sources (p = 0.026). Information goals at time 1 predicted information seeking at time 2 (p = 0.014). Information needs at time 1 did not predict information seeking at time 2 (Disease Orientated information need p = 0.084, Action Orientated information need p = 0.229). Cognitive Avoidance at time 1 was negatively associated with the number of information sources accessed at time 2 (p = 0.046). This relationship became a non‐significant trend (p = 0.066) when baseline information seeking was controlled for. No other adjustment style (at time 1) exhibited a significant relationship with information seeking at time 2. Conclusions These findings suggest that information seeking may vary as a function of adjustment to cancer. Consequently, information provision to patients could be more appropriately tailored by attending to how a patient is adjusting to their diagnosis of cancer. Copyright © 2012 John Wiley & Sons, Ltd.